2005
DOI: 10.1093/eurpub/cki164
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health in early adulthood: what is the role of parental education, childhood adversities and own education?

Abstract: Childhood living conditions and adversities are strongly associated with poor SRH and psychological distress in early adulthood. Early recognition of childhood adversities followed by relevant support measures may play an important role in preventing health problems in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 51 publications
3
67
2
4
Order By: Relevance
“…[40] Socioeconomic disadvantage may shape youths' mental health in several ways: (1) through the lasting effects of early life experiences, (2) through influences on academic and socioeconomic attainment, (3) through direct biological mechanisms. In this study, we accounted for the first mechanism by controlling the analyses for family disruption, [3,41] parental physical and mental illness, [42] and family conflict. [43] Our results indicated that, with the exception of family disruption which previously has not been consistently associated with long-term patterns of mental health, [42] these factors were associated with youths' mental health in univariate analyses, but did not explain the effect of longitudinal family income.…”
Section: Socioeconomic Factors and Youths' Internalizing Symptomsmentioning
confidence: 99%
“…[40] Socioeconomic disadvantage may shape youths' mental health in several ways: (1) through the lasting effects of early life experiences, (2) through influences on academic and socioeconomic attainment, (3) through direct biological mechanisms. In this study, we accounted for the first mechanism by controlling the analyses for family disruption, [3,41] parental physical and mental illness, [42] and family conflict. [43] Our results indicated that, with the exception of family disruption which previously has not been consistently associated with long-term patterns of mental health, [42] these factors were associated with youths' mental health in univariate analyses, but did not explain the effect of longitudinal family income.…”
Section: Socioeconomic Factors and Youths' Internalizing Symptomsmentioning
confidence: 99%
“…Even though the youngest age groups are healthier than others, one fourth of all 18-to 29-year-olds has a chronic illness, and one third rates their physical fitness to be average at best Kestilä et al 2006). Prolonged unemployment is known to decrease the functional capacity of even the young.…”
Section: Introductionmentioning
confidence: 99%
“…Among the socio-economic circumstances, early living conditions are important, as childhood adversities may have both direct and indirect effects on adult health (Galobardes et al, 2006;Kestilä et al, 2006;Kivimäki et al, 2006a, b;Mäkinen et al, 2006) and on mortality (Galobardes et al, 2004). However, childhood socio-economic position has often been examined irrespective of current socio-economic position.…”
Section: Introductionmentioning
confidence: 99%